Dikotomi Ilmu Dalam Pendidikan Islam - Majida Faruk; Radjiman Ismail; H. Moh.Natsir Mahmud (Peneliti.net, 2023)
Islam has universal teachings that govern the affairs of the world and the hereafter. Errors in understanding the teachings of Islam result in the emergence of an attitude that glorifies one science over another. This study aims to discuss the dichotomy of science in Islamic education. The emergence of dichotomies in Islamic education has a negative effect on non-conceptual sources as authoritative sources to explain the true truth. The loss of a rationalistic scientific thinking culture among Muslims which is characterized by liberal, open, innovative and constructive. In fact, there are many other negative impacts caused by the dichotomous attitude in Islamic education. In conclusion, there is no scientific dichotomy in Islam as has been widely discussed until now. Islam only informs us that some knowledge comes from revelation and some is the result of human scientific thinking, both of which are basically sourced from Allah SWT. Islam integrates all aspects of life in the educational process. There is no separation of life problems and separation of fields of knowledge. Islam views that humans must be perfectly educated by integrating all approaches.